خصوصية عقد حفظ الحق في نشاط الترقية العقارية وفقا للتشريع الجزائري - دريس, كمال فتحي (جامعة الوادي University of Eloued, 2019)
ملخص: سعت الجزائر ولا تزال للقضاء على أزمة السكن أين رفعت احتكارها على هذا القطاع وسمحت للخواص الاستثمار في هذا المجال والمساهمة في عمليات الترقية العقارية. كما قنن المشرع الجزائري نشاط الترقية العقارية بهدف تحفيز القطاع الخاص للاستثمار فيه، واستحداث صيغ حديثة للتعاقد مع المرقي العقاري لاقتناء السكنات وعلى رأسها عقد البيع على التصاميم وعقد حفظ الحق، هذا الأخير الذي قل ما يتم التعامل به، الأمر الذي يستدعي البحث في نظامه القانوني من خلال تحليل النصوص القانونية ذات الصلة والوقوف عند خصوصيته والضمانات التي كفلها المشرع للأطراف، محاولة للوقوف عند أسباب عدم التعامل بهذه الصيغة. APSTRACT : Algeria has sought and continues to eliminate the housing crisis where it has raised its monopoly on this sector and allowed the private sector to invest in this area and contribute to the process of real estate promotion. The Algerian legislator has also legalized the promotion of real estate in order to stimulate the private sector to invest in it, and the update of modern formulas to contract with the real estate promoter for the housing acquisition, especially the contract of sale on the designs and the preservation of the rights, the latter, which is less dealt with, which calls for research in the legal system through the analysis of the relevant legal texts and focusing on its privacies and guarantees that is given by the legislator to the parties, as an attempt to identify the reasons for not dealing with this formula.
The Privacy Of The Right Preservation Contract In Terms Of Real Estate Promotion Activity According To The Algerian Legislation
Keywords: نشاط الترقية العقارية ; عقد حفظ الحق ; المرقي العقاري ; السعر التقديري للبيع; Real Estate Promotion Activity ; preservation of the rights ; Real Estate Promoter ; Estimated Price for Sale